Effects of transcranial direct current stimulation on the working memory of post-stroke people: an integrative review - Filho, Edson Meneses da Silva; Albuquerque, Jéssica Andrade de; Mescouto, Karime Andrade; Freitas, Rodrigo Pegado de Abreu (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Stroke is a chronic disease that is becoming more common in all the world causing damage to people affected, for instance, cognitive deficits. The Transcranial Direct Current Stimulation (tDCS) is a form of treatment that modulates specific areas of the nervous system. Objective: The objective of this integrative review was to analyze the effectiveness of Transcranial Direct Current Stimulation (tDCS) on the working memory (WM) in post-stroke patients. Method: This review included articles that analyzed the effects of tDCS on human beings with a diagnosis of stroke and used as outcomes: verbal, visual, spatial or auditory WM. The assessment of studies elegibility was performed by two independent researchers from 8 databases: Cochrane Library via Wiley - CENTRAL, PubMed, LILACS, SCIELO, Web of Science, Scopus, CINAHL and PEDro following PRISMA guideline. Results: Three articles were included in the qualitative synthesis presenting a total of 66 participants (32 male and 34 female), 36 ischemic stroke and 30 hemorrhagic stroke with an average time of 42 days. Interventions were done on the areas F3/F4 (dorsolateral part of the prefrontal cortex) and T3/T4 (temporal anterior lobe) with 2mA current intensity for 30 minutes duration. The outcomes analyzed: verbal, visual, spatial, and auditory WM showed significant improvements after the use of tDCS. Conclusion: The limitations of this review were study designs, number of participants, lack of standardized interventions and short period of follow-up. tDCS showed satisfactory results on the WM of post-stroke individuals, but it is needed to be cautious due to the methodological quality of the articles. It is registered in the Prospective Register of Systematic Reviews - PROSPERO with registration number CDR42016048050.